2011
DOI: 10.2214/ajr.10.5763
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution MR Neurography: Evaluation Before Repeat Tarsal Tunnel Surgery

Abstract: MRN yields accurate morphologic information about the location and extent of nerve injury after failed tarsal tunnel release and facilitates preoperative diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…A 43-year-old male with recent knee injury (reported as "calf rupture" by the patient), presenting with calf pain and weakness. 21 Although, the experience of the authors is ever increasing in the interpretation of these specialized exams, the abnormal nerves show one or a combination of the following findings: T2 hyperintensity approaching the adjacent vascular signal intensity, nerve enlargement, focal neuroma formation, fascicular enlargement or disruption, contour alterations or course deviations. MRN was performed to evaluate tibial nerve and CPN.…”
Section: Figmentioning
confidence: 99%
“…A 43-year-old male with recent knee injury (reported as "calf rupture" by the patient), presenting with calf pain and weakness. 21 Although, the experience of the authors is ever increasing in the interpretation of these specialized exams, the abnormal nerves show one or a combination of the following findings: T2 hyperintensity approaching the adjacent vascular signal intensity, nerve enlargement, focal neuroma formation, fascicular enlargement or disruption, contour alterations or course deviations. MRN was performed to evaluate tibial nerve and CPN.…”
Section: Figmentioning
confidence: 99%
“…With current high-resolution techniques, magnetic resonance imaging of the nerves known as MR neurography (MRN) can, in a non-invasive, accurate and reliable way, demonstrate normal and abnormal nerve and regional muscle denervation with good surgical correlation [5][6][7]. The MRN technique requires expertise in protocoling, post-processing and interpretation [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Chhabra et al (5) reported that the preoperative evaluation in 90% of patients before repeat TTR revealed nerve repeat entrapment related to focal fibrosis using high-resolution magnetic resonance neurography (MRN). The injured nerves could be visualized using MRN, with a sensitivity of 77% for the tibialis posterior nerve, 100% for the medial plantar nerve, and 100% for the lateral plantar nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients' symptoms will disappear with operative decompression; however, the symptoms can persist, recur, or become worse in some. Throughout the published data, reports have been made of the variable outcomes of tarsal tunnel release (TTR) (2,4,5). The failure rate of TTR has ranged from 4% to 56% (1,2,6,7).…”
mentioning
confidence: 99%